Meta-Analysis of Children’s Moral Education in the Digital Era: A Bibliometric Analysis (1977-2021) - Marhani; Astuti, An Ras Try (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study uses bibliometric methods to conduct a meta-analysis of research on children’s moral education in the digital era, published between 1977 and 2021. The study analyzes literature to address questions related to children’s moral education in a digitalized society, where digitalization affects various aspects of social life and changes ways of thinking and living. The bibliometric analysis excludes the year 2022. Data was collected to examine the contributions of various authors, research institutions, and countries in this field. The analysis identifies key authors contributing to the field, with Cooney, M., Firth, A., and Herman-Pillath, C. being the most prolific. Leading research institutions include Delft University of Technology, City University of New York, and Cornell University. The United States, the United Kingdom, and China are the top contributing countries. The study also visualizes the types of documents published, with articles being the most common (48.6%), followed by book chapters (27.6%), books (10.0%), reviews (9.0%), conference papers (2.1%), editorials (2.1%), and notes (0.7%). This study highlights the importance of moral education in the digital era, emphasizing that effective methods—such as best practices, socialization, counseling, mindfulness, humor, and supervision—are crucial for children to navigate digital media responsibly. The findings provide valuable insights for families, educators, and policymakers to enhance moral education strategies in a rapidly evolving digital landscape.